Justiça restaurativa: limites e desafios da integração comunitária na contemporaneidade - Giordani, Miriel Carine (2018)
The present dissertation is about community integration in Restorative Justice in contemporary times. Its objective is to investigate how community participation in restorative justice can be limited and challenged by characteristics of contemporary society such as individualism, absence of community sense, liquidity of social relations, freedom in its negative dimension and depoliticization. First, the study addresses the historical origin and conceptual nature of Restorative Justice, as well as its relation to the traditional criminal system. Following are the forms of community participation in restorative processes, the theoretical justifications that legitimize the community experiences in conflict resolution and exposes some key terms that link Restorative Justice to the social scene, such as concepts of citizenship, community and social capital. In a third, the work identifies how certain characteristics of contemporary society limit and challenge community participation in Restorative Justice. Substantially characteristics of contemporary society are able to impose limits, challenges and even render unfeasible the goal of community participation in conflict resolution, as they negatively influence the modern individual and the community environment idealized by Restorative Justice. It is basic (theoretical) research through the procedures used as bibliographical and documentary. Also for the purposes of the research to be achieved, the hypothetical-deductive scientific method is used. The line of research adopted is State, Society and Development Policies.